From Small to Stellar: SDN Temenggungan's Journey Towards National Standards and 'Merdeka Belajar' - Hariyadi, Slamet; Subaharianto, Andang; Siswati, Bea Hana (Universitas Lambung Mangkurat, 2025)
SDN Temenggungan, a public elementary school in the center of Banyuwangi City, faces various challenges related to parental participation, limited facilities, and conflicts with the local community. The community service program that was implemented was planned for two years with the aim of improving the quality of education in this school through the implementation of the Independent Learning Curriculum (Kurmer). In the first year, the program focused on teacher training, curriculum development, and increasing parental participation. The community service method used was participatory action, involving all related parties actively in the process of diagnosing problems, planning actions, implementing, evaluating, and specifying recommendations. The results of the activities showed that the implementation of Standards 1-4 went well, teachers successfully implemented innovative teaching methods, and students showed increased participation. Although social and economic challenges still exist, significant progress has been made in creating a more inclusive learning environment and supporting student development. This program provides a strong foundation for schools to continue to improve the quality of education and overcome future challenges.